THE INFLUENCE OF HUDUD LAW IN SHAPING LEGAL AWARENESS AND CRIME PREVENTION IN SOCIETY - Yahya, Roby Putra; Farid, Diana; Abdulah Pakarti, Muhammad Husni; Hendriana, Hendriana; Hasan, Muhammad Farid (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2023)
Hudud punishment is a legal system based on religion and is applied in several countries that adhere to Islam. This punishment is included in the category of very harsh punishments, such as stoning, flogging, and amputation. In this context, this abstract aims to investigate the influence of Hudud Punishment on the formation of legal awareness and crime prevention in society. This study uses a descriptive- analytical method which involves secondary data analysis in the from of literature, research reports, and case studies that are relevant to the themes discussed. The findings of this study demonstrate the complex and multi-dimensional influence of Hudud Punishment of legal awareness and crime prevention in society. In this context, legal awareness and effective crime prevention do not only depend on a strict legal system, but also require a holistic and comprehensive approach. In the context of Hudud Punishment, the need for a moral values and empower communities in facing legal challenges. Overall, this research highlights the importance of considering broader factors in shaping legal awareness and crime prevention in society. Strict legal systems such as the Hudud Penalty can play an important role in providing a deterrent effect and reducing crime, but they also pos complexities and challenges that nedd to be overcome. In facing this challenge, and approach based on a deep understanding of law and human values is the key to achieving better legal awareness and preventing crime in society.